Integrated chemical and biological assessment of contaminant impacts in selected European coastal and offshore marine areas. (March 2017) - Hylland, Ketil; Robinson, Craig D.; Burgeot, Thierry; Martínez-Gómez, Concepción; Lang, Thomas; Svavarsson, Jörundur; Thain, John E.; Vethaak, A. Dick; Gubbins, Mattew J.
Abstract: This paper reports a full assessment of results from ICON, an international workshop on marine integrated contaminant monitoring, encompassing different matrices (sediment, fish, mussels, gastropods), areas (Iceland, North Sea, Baltic, Wadden Sea, Seine estuary and the western Mediterranean) and endpoints (chemical analyses, biological effects). ICON has demonstrated the use of a framework for integrated contaminant assessment on European coastal and offshore areas. The assessment showed that chemical contamination did not always correspond with biological effects, indicating that both are required. The framework can be used to develop assessments for EU directives. If a 95% target were to be used as a regional indicator of MSFD GES, Iceland and offshore North Sea would achieve the target using the ICON dataset, but inshore North Sea, Baltic and Spanish Mediterranean regions would fail. Highlights: A framework for integrated assessment of contaminant impacts in marine areas has been developed and demonstrated. It is necessary to include both chemical analyses and biological effects in an assessment of contaminant impacts. Only two of the areas, Iceland and offshore North Sea, would have "Good Environmental Status" using MSFD criteria.